CURRICULUM INTEGRATION IMPLEMENTATION MODEL: INDEPENDENT CURRICULUM DINIYAH - Fathurrahman, Fathurrahman; Amalia, Nabila Shovi; Ulul Albab, Hayyan Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Efforts to integrate the curriculum were a strategy to combine various learning materials into subject units. This study investigates the curriculum implementation model employed the Nahdlatul Ulama Elementary School (SDNU) Banat Banin Lamongan which successfully combined the independent curriculum, the madrasah diniyah curriculum, and the Al-Qur'an for pre-elementery school or Taman Pendidikan Al-Qur’an (TPQ) curriculum for their instruction. Meanwhile, the research design employs descriptive qualitative method, the data were obtained through interview, observation and documentation and then processed using qualitative interactive analysis through the stages of data condensation, data exposure and drawing conclusions. The research results show that the curriculum integration implementation model carried out by SDNU Banat Banin Lamongan includes 3 models; first, the school curriculum is a combination of the implementation of the independent curriculum plus the Madrasah Diniyah curriculum and the Al-Qur'an for pre-elementary school; second, implementing curriculum integration in the form of combining various learning materials into a learning theme; third, the use of interactive learning methods and media applied by teachers in the instruction.